Use of algorithms for high quality diagnostics and handling of patients with autoimmune rheumatic diseases - Wiik, Allan (Henry Stewart Talks, 2007)
Tests to diagnose autoimmune rheumatic diseases, Parameters to indicate clinical value of test results, Tests based on different technologies, Making diagnostics clinically appropriate, Algorithms for use in family practice and in rheumatology practice, Detection of early autoimmune disease, Value for money has to be based on optimal early diagnostic work-up
Archived at 2018/05/31